International Marriage for Homogeneity? - Evidence from Marriage Migration in South Korea - Seo-Young Cho (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
This paper investigates empirically whether cultural, racial, and linguistic similarities increase marriage migration. By using marriage migration data from South Korea, I find that the similarities between an origin country and South Korea pull more marriage migration, but the positive effects of the similarities are mainly driven by female marriage migrants from middle and low income countries. The pulling effects of the similarities can be explained by female deficits in the marital age group in South Korea that motivate Korean men to seek foreign brides who share similar traits with locals.
Keywords: F2; J1; O5; 330; Marriage Migration; Similarities; Sorting Traits; Demographic Changes; and South Korea